Egg mimicry in Cuckoos parasitizing four sympatric species of Acrocephalus Warblers - Edvardsen, Erik; Moksnes, Arne; Roskaft, Eivin; Oien, Ingar J; Honza, Marcel (The Condor (Los Angeles, Calif.), 2001)
The Cuckoo (Cuculus canorus) is an interspecific brood parasite that mimics the eggs of its hots. In this study we tested the resemblance between cuckoo and host eggs in four host species breeding in sympatry: the Reed Warbler (Acrocephalus scirpaceus)(, Great Reed Warbler (A. arundinaceus), Sedge Warbler (A. schoenobaenus), and Marsh Warbler (A. palustris).